2016
DOI: 10.4236/fns.2016.710092
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Functional Food Product Using Guavas

Abstract: The global market of functional foods and demand for a healthy lifestyle among consumers in recent years is growing. Guava is a highly perishable fruit and a rich source of vitamin C. Guava Cheese (GC) is a semi-solid concentrated fruit product that could be consumed as a snack. The objectives were to develop a guava cheese (GC) and determine the antioxidant potential of the product. Formulation consisted of guava puree with added sucrose or agave, chia seeds and almonds. Pectin was added at select concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Total antioxidant capacity (TAC) of extruded samples was measured using an adapted method of Patel et al [24]. The methanol extracts from the TSP were used in this evaluation.…”
Section: Total Soluble Phenolics and Total Antioxidant Capacity Of Fi...mentioning
confidence: 99%
“…Total antioxidant capacity (TAC) of extruded samples was measured using an adapted method of Patel et al [24]. The methanol extracts from the TSP were used in this evaluation.…”
Section: Total Soluble Phenolics and Total Antioxidant Capacity Of Fi...mentioning
confidence: 99%
“…It is usually processed like jam with the texture firm enough to be moulded and sliced (Bramwell and Badrie, 2002). Fruits like pineapple, papaya and banana, apple, pear and plum have been utilized for preparation of fruit cheese (Bramwell and Badrie, 2002;Srivastava and Kumar, 2010;Kuchi et al, 2014;and Patel et al, 2016). However, very little work has been carried out on mixed fruit cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research efforts have been made in the past for developing fruit cheese from different fruits. These include preparation of guava cheese with varying concentrations of pectin (0, 0.5, 1 and 1.5 %) by Patel et al (2016). Rahul et al (2019) studied sensory qualities of guava-jamun cheese and observed that cheese prepared with 20 per cent guava and 80 per cent jamun pulp blends was found most acceptable with respect to colour and appearance (8.20), flavour (8.10), texture (8.10), taste (8.10) and overall acceptability (8.12).…”
Section: O N L I N E C O P Ymentioning
confidence: 99%